Analisis Implementasi Konsep Nafkah dalam Upaya Meningkatkan Kesejahteraan Perekonomian Keluarga di Desa Karangsari Kecamatan Kembaran Kabupaten Banyumas - Shofiyulloh Syaubari (el-Jizya : Jurnal Ekonomi Islam, 2021)
Karangsari Village is a village located in the Banyumas Regency, Central Java. From existing data, one third of the population is in the poverty line. Even though almost all of its territory is relatively fertile agricultural land, but it is not supported by quality human resources, due to the low level of education due to dropping out of school. from this it can be concluded that When the head of the family has a low education, the impact is that the provision of a living is the main axis in building family welfare. This study critically analyzes the responsibilities of a husband as the head of the family in his role in realizing the family's economic welfare. The responsibility to provide a living is a consequence that must be carried out by the husband after the marriage. In other words, this study aims to provide a general view that the implementation of a living is considered capable of alleviating poverty in the family environment. The more a husband realizes the obligation of living and tries to fulfill it, it means that he can build and nurture a family well in economic prosperity. Through the analysis of basic needs, this study traces the economic welfare of the family which is influenced by the awareness of the responsibilities of living, which includes the needs of clothing, food and housing. The implication of this research is the necessity to optimize the concept of living in improving the economic welfare of the family.